Posttraumatic stress disorder is characterized by functional dysregulation of dermal fibroblasts - van de Vyver, M.; Benecke, R.M.; van den Heuvel, L.; Kruger, M.J.; Powrie, Y.; Seedat, S.; Smith, C. (Biochimie, 2024)
Incidence of mental health disorders are rising in modernity, with psychological stress linked to a propensity for developing various chronic diseases due to a relative inability of the body to counter the allostatic load on cellular level. Despite these high rates of comorbidities associated with posttraumatic stress disorder (PTSD), there is still a lack of understanding in terms of the peripheral effects of PTSD on tissue level. Therefore, the purpose of this study was to profile basal dermal fibroblast functional status in PTSD using a wide range of markers involved in the cell-to-cell communication facilitated by fibroblasts. Primary dermal fibroblasts derived from patients diagnosed with PTSD (n = 11) and matched trauma exposed controls (i.e. who did not develop PTSD, n = 10) were cultured using standard techniques. The patients and controls were matched based on age, sex, body-mass index (BMI) and lifestyle. The growth rate, population doubling time, cell surface marker expression (CD31, FNDC5) (flow cytometry), secretome (TIMP-2, MMP-9) (ELISAs), intracellular signalling capacity (Fluo-4 Ca2+ flux) and gene expression (IL-6, IL-10, PTX-3, iNOS, Arg1) were compared between groups. The data illustrated significant PTSD-associated fibroblast conditioning resulting in a blunted signalling capacity. This observation highlights the importance of including tissue-specific investigations in future studies focused on elucidating the association between PTSD and subsequent risk for somatic disease. •PTSD conditions fibroblasts in the periphery.•Fibroblast signalling capacity is generally blunted in PTSD.•Data suggest PTSD-associated fibroblast desensitization to stimuli.